Ambiguity in Different Types of Question Translation: An Experimental Analysis - Vikram, Shweta; Dwivedi, Sanjay K (International Journal of Computer Sciences and Engineering, 2025)
In Word Sense Disambiguation (WSD) much research has been carried out and are still being made today. If a sentence has ambiguity or ambiguous word, then the meaning of this sentence may or may not differ from context. If the meaning of the sentence is inferred from the context, then the concept of WSD comes to remove the ambiguity. Here we will discuss ambiguity which comes after Machine translation. In our experiment, we have collected different types of questions for analyzing the impact of ambiguity for wh-questions with respect to other questions (objective, match, fill in the blank and keyword specific). Some machine translators do not understand the type of the question and treated as a normal question/sentence. In this paper, we will discuss the five different types of questions and their machine translation with five standard online/offline translators. This paper describes our work on the impact of ambiguity from English to Hindi translation of different types of questions and main focus on wh-questions versus other questions translation. In this paper also have some experimental analysis and their result